2000
DOI: 10.1007/s007020070088
|View full text |Cite
|
Sign up to set email alerts
|

Growth-associated protein GAP-43 in the frontal cortex and in the hippocampus in Alzheimer's disease: an immunohistochemical and quantitative study

Abstract: We studied the growth-associated protein, GAP-43 (also called neuromodulin and B-50) in post-mortem brain tissue using immunohistochemistry and quantitative Western blotting, from patients with Alzheimer's disease (AD) and age-matched control subjects. By immunohistochemistry, we found a clear reduction of GAP-43 in the frontal cortex, while in the hippocampus, there was a marked reduction in some areas (dentate molecular layer, stratum moleculare and radiale of CA1 and CA4), while not in other areas (stratum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
38
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 40 publications
11
38
3
Order By: Relevance
“…The model used by Kerschensteiner was a single focused targeted lesion using cytokines in the Lewis rat showing an acute monophasic pathology. Similar results have been found in MS lesions [33] and in the brains of Alzheimer's patients [34], reflecting a loss of plasticity of functionally impaired neurones. Furthermore, severe CNS injury in mice leads to diminished GAP-43 expression, reflecting the loss of endogenous repair mechanisms [35].…”
Section: Discussionsupporting
confidence: 85%
“…The model used by Kerschensteiner was a single focused targeted lesion using cytokines in the Lewis rat showing an acute monophasic pathology. Similar results have been found in MS lesions [33] and in the brains of Alzheimer's patients [34], reflecting a loss of plasticity of functionally impaired neurones. Furthermore, severe CNS injury in mice leads to diminished GAP-43 expression, reflecting the loss of endogenous repair mechanisms [35].…”
Section: Discussionsupporting
confidence: 85%
“…Previously experiments showed that GAP-43 was also significantly lower in aged rats in the frontal cortex [21]. However, we did not find catalpol increase GAP-43 protein levels in frontal cortex, which suggested that catalpol may mainly affect hippocampal neuroplasticity.…”
Section: Catalpol Increases Spatial Performance and Behavior Responsecontrasting
confidence: 88%
“…The results of western blotting were consistent with the immunohistochemical results, i.e., increased levels of GAP-43 in hippocampus. Previous analysis has shown that GAP-43 is significantly lower in aged rats than controls in the hippocampus [21]. The finding is supported by the majority of studies investigating the levels of GAP-43 in various brain regions of AD patients [22,23].…”
Section: Catalpol Increases Spatial Performance and Behavior Responsesupporting
confidence: 53%
See 1 more Smart Citation
“…[132][133][134] In AD brain, GAP43 is found in the dystrophic neurites in plaques. 135,136 GAP43 protein levels are decreased in the frontal cortex and the hippocampus in AD. [137][138][139] GAP43 is secreted to the CSF at which it serves as a potential marker for synaptic degeneration or plasticity.…”
Section: Gap43 (Neuromodulin)mentioning
confidence: 95%